Is traumatic stress a vulnerability factor for women with substance use disorders? - Hien, Denise (2005)
The primary goal of this paper is to review existing findings from trauma, addictions and developmental research in order to delineate salient and outstanding questions for future research in this field. Toward this aim, our manuscript will provide an overview of the extant body of knowledge of trauma/PTSD comorbidity with substance use disorders and draw attention to converging developmental and neurobiological literature on the consequences of trauma on self-regulation. We conclude with suggestions for future research in these areas.